Urban collectives and social media: promoting insurgency to cope with covid-19 in informal setlements | Coletivos urbanos e insurgência para combater a covid-19: uma análise de conteúdo de mídias digitais - Furtado, Lara Sucupira; Furtado, Lia Sucupira (Oculum Ensaios, 2021)
The high incidence of COVID-19 cases in low-income communities, the context of disinformation around the disease, and the vacuum of public policies have made low-income communities more vulnerable to the pandemic. Considering that scenario, this paper analyzes how urban collectives have used social media to create and share narratives about COVID-19. We frame those contributions through the lens of insurgency, an area of planning studies that is based on grassroots counter-hegemonic actions. We conduct a sentiment and thematic analysis of Instagram posts from urban collectives in Fortaleza to show how social media has been appropriated as a space to cope with the virus and to support insurgency. Our findings show, even though most strategies are geared towards emergency relief, collectives also harness the atmosphere of crisis brought by covid-19 to raise awareness of other structural issues. Collectives promote insurgency by creating their own content, information, and research material about COVID-19 in their communities and by partnering with institutions to scale up their claims.